The correlation between the amount of weight gain and physical activity levels in Depot Medroxyprogesterone Acetate (DMPA) users - Hasanah, Zumroh; Merawati, Desiana; Azidin, Raja Mohammed Firhad Raja; Amelia, Dessy; Puriastuti, Alifia Candra; Novembriani, Rizqie Putri; Viandika, Nurya; Dewi, Putri Nurika (Universitas Negeri Malang, 2025)
Background: DMPA is a widely used contraceptive in Indonesia due to its accessibility and effectiveness. However, side effects such as weight gain are a concern, with more than 90% of the 600 users in 2022-2023 experiencing them. Objective: This study aimed to examine the correlation between the amount of weight gain and physical activity levels in DMPA users. Methods: This study used a cross-sectional design with consecutive sampling, involving 82 women (aged 19-51 years, average weight 58 kg) selected using the Slovin formula. Data were collected through structured interviews and questionnaires covering demographics, medical history, and physical activity level based on IPAQ. Body weight was measured with a calibrated digital scale, and association analysis was performed using the Chi-Square test (p < 0.05 was considered significant). Result: Analysis showed no statistically significant association between physical activity level and the amount of weight gain in DMPA users (p > 0.05). Conclusion: Other factors beyond physical activity, such as diet and metabolism, may play a more significant role in weight gain in DMPA users, so further research is needed. Future research should clarify these relationships by considering a broader range of influencing factors, including demographic variables, metabolic health, lifestyle behaviors, etc., to develop a more comprehensive understanding of how DMPA use affects weight management.